PENGARUH KINERJA KEUANGAN DAN STRUKTUR KEPEMILIKAN TERHADAP RETURN SAHAM - Islamiya, Maesa Kharisma Okta; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out the influence of financial performance and Good Corporate Governance to the stock return. The independent variables of this research are return on assets, debt to equity ratio, total assets turnover, structure of managerial ownership, and structure of managerial institutional. Meanwhile, the dependent variable of this research is stock return.This research has been conducted by using purposive sampling which selects sample with the criteria which has been determined by the researcher. Based on the research method, 63 samples of 21 manufacturing companies which are listed in Indonesia Stock Exchange (IDX) with periods of 2012-2014 have been selected as samples. The analysis method has been done by using multiple linear regressions analysis.The result of goodness of fit shows that the variables of return on asset, debt to equity ratio, total assets turnover, structure of managerial ownership, and structure of managerial institutional is the explanatory variables from the stock return. The result of hypothesis test shows that the variable of Return on Asset has significant positive to the stock Return, meanwhile Debt to Equity Ratio, Total Asset Turnover, structure of managerial ownership, and structure of managerial institutional do not have any influence to the stock return.Keywords: Financial performance, good corporate governance, stock return